Effectiveness of Chest CT in Children: CT Findings in Relation to the Clinical Question - Esser, Michael; Tsiflikas, Ilias; Kraus, Mareen Sarah; Hess, Sabine; Gatidis, Sergios; Schaefer, Jürgen F. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Purpose To estimate the effectiveness and efficiency of chest CT in children based on the suspected diagnosis in relation to the number of positive, negative, and inconclusive CT results.Materials and Methods In this monocentric retrospective study at a university hospital with a division of pediatric radiology, 2019 chest CT examinations (973 patients; median age: 10.5 years; range: 2 days to 17.9 years) were analyzed with regards to clinical data, including the referring department, primary questions or suspected diagnosis, and CT findings. It was identified if the clinical question was answered, whether the suspected diagnosis was confirmed or ruled out, and if additional findings (clinically significant or minor) were detected.Results The largest clinical subgroup was the hematooncological subgroup (n = 987), with frequent questions for inflammation/pneumonia (66 % in this subgroup). Overall, CT provided conclusive results in 97.6 % of all scans. In 1380 scans (70 %), the suspected diagnosis was confirmed. In 406/2019 cases (20 %), the CT scan was negative also in terms of an additional finding. In 8 of 9 clinical categories, the proportion of positive results was over 50 %. There were predominantly negative results (110/179; 61 %) in pre-stem cell transplant evaluation. In the subgroup of trauma management, 81/144 exams (57 %) showed positive results, including combined injuries (n = 23). 222/396 (56 %) of all additional findings were estimated to be clinically significant.Conclusion In a specialized center, the effectiveness of pediatric chest CT was excellent when counting the conclusive results. However, to improve efficiency, the clinical evaluation before imaging appears crucial to prevent unnecessary CT examinations.Key Points: Citation Format
Keywords: thorax; CT-spiral; pediatrics